2003
DOI: 10.1056/nejmoa022794
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Chemotherapy with Hematopoietic Stem-Cell Rescue for High-Risk Breast Cancer

Abstract: High

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
158
2
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 228 publications
(170 citation statements)
references
References 21 publications
6
158
2
4
Order By: Relevance
“…Patients received the cyclophosphamide, thiotepa and carboplatin (CTC) high-dose chemotherapy regimen with peripheral blood progenitor cell transplantation as described previously (Rodenhuis et al, 1996(Rodenhuis et al, , 1999(Rodenhuis et al, , 2003Schrama et al, 2001). Patients had either high-risk primary breast cancer and received high-dose chemotherapy as part of their adjuvant treatment, or had advanced breast, germ-cell or ovarian cancer.…”
Section: Patients and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients received the cyclophosphamide, thiotepa and carboplatin (CTC) high-dose chemotherapy regimen with peripheral blood progenitor cell transplantation as described previously (Rodenhuis et al, 1996(Rodenhuis et al, , 1999(Rodenhuis et al, , 2003Schrama et al, 2001). Patients had either high-risk primary breast cancer and received high-dose chemotherapy as part of their adjuvant treatment, or had advanced breast, germ-cell or ovarian cancer.…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…The full-dose CTC regimen consisted of 4 days of chemotherapy with cyclophosphamide (1500 mg m À2 day À1 ) as a 1 h infusion, immediately followed by carboplatin (400 mg m À2 day À1 ) as a daily 1 h infusion, and thiotepa (120 mg m À2 day À1 ) divided over two 30-min infusions (the second daily dose of TT was administered 12 h after the first dose) (Rodenhuis et al, , 2003. The 'tiny' CTC regimen (tCTC) was identical to the CTC regimen except that it incorporated 2/3rd of the dose of each agent (Rodenhuis et al, 1996(Rodenhuis et al, , 1999Schrama et al, 2001).…”
Section: Patients and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of his treatment he received one course of high-dose chemotherapy with autologous peripheral blood progenitor cell transplantation, consisting of cyclophosphamide (1,500 mg/m 2 day ¡1 ) as 1-h infusion, immediately followed by carboplatin [dose calculated based on modiWed Calvert formula: AUC (mg min/mL) = Dose (mg)/(CL cr (mL/min) + 25) with 5 mg min/mL as daily target AUC] as 1-h infusion and thiotepa (120 mg/m 2 day ¡1 ) divided over two 30-min infusions 12 h apart, for four consecutive days. Full details of the CTC regimen have been published previously [17].…”
Section: Casementioning
confidence: 99%
“…In high-risk breast cancer, there are negative trials showing no superiority for high-dose chemotherapy (Bergh et al, 2000;Hortobagyi et al, 2000;Tallman et al, 2003); in contrast, other trials have shown significant improvement in relapse-free and overall survival (Roche et al, 2003;Rodenhuis et al, 2003;Nitz et al, 2005). In metastatic breast cancer, whereas some trials have failed to demonstrate a survival benefit, others have suggested an advantage in event-free survival in favour of high-dose treatment (Stadtmauer et al, 2000;Crown et al, 2004;Lotz et al, 2005;Schmid et al, 2005).…”
mentioning
confidence: 99%